Scnenic-eternal ephemeral continuity in the actors’s work (PesquisAtor, 2013)
The art of the actor, different from what they suppose much, it has no end. It is harnessed to the Beginning of Continuity, corresponding so to the Semiotics of Charles Sanders Peirce. His distance is one to tread esthetically in constant change. A continuous chain that does not end, even after the first night. The question differs regarding the activity of the playwright, which, while producer of “fixed, passive, inert and deaf” language, has his placed text, horizontally, in the shelves of the libraries, I subject to a simple reading until it is (or not) revitalized by the Poets of Dioniso. The toil of the Wandering one of Wooden box is vertical and it is already born dying. It is ephemeral, deslocável, sequential and liquid. So being, we have evanescência for the interpreter and durability for the author; imediatismomediatismo; instantaneousness-wait; presentidade-eternity, respectively. No artist has so full certainty of which his operations of “manufacture“ are tracks of volatizações constant like the actor, bearer of an artistic method resided in the unfinished one. He suffers a perturbable confrontation with the time, without leaving place for the absolute thing. Ready show, it does not mean that I end, because what is kinetic, what is dynamic and what is in the contemporaneousness of you himself, for the nature itself, is subject to constant modifications. Now, the same character who energized was yesterday on the stage, today, is already different, because we are also different to each day, in perishable support, like the life. On the other side, we are not in telling doing an acting to each night. This is a chaos and it has a tendency to drive mad the cast, inducing the assembly to the shipwreck. We propagate the reiteration of the same score, with consecutive re-creation. It is to be able to make the “ancient acquaintance” into “unknown original”. A play! A strategy! A master-stroke! If there is certain mistake in that interpreter who judges to have reached, in the first night, the end of his Process of Creation, there is mistake also in that what understands not to need so much work, at once that his activity is fluid. On the contrary, how much more liquidity, more investment in studies, field works and bibliographical, leituras, exercises, refined and exhaustive formation of the technical equipment, of the construction of a repertoire that notices so great volatility.